2023
DOI: 10.29333/ejmste/13346
|View full text |Cite
|
Sign up to set email alerts
|

Chinese mathematics teachers’ TPACK and attitudes toward ICT integration in the post-pandemic era

Abstract: This study investigated primary mathematics teachers’ technological, pedagogical, and content knowledge (TPACK) and attitudes towards information and communication technology (ICT) integration in mainland China during the post-pandemic period. Quantitative data were collected through a web-based self-determined questionnaire. Statistical analysis was performed using independent sample t-tests, and Mann-Whitney U tests to assess gender and teaching experience in years. Spearman’s correlation test also examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Principals must play multiple roles to keep the institutions running, manage teachers and students, and implement and manage curriculum change. Technology integration in education is an idea far from new, but technology in teaching mathematics still faces various challenges (see Abdullah et al, 2016;Daher et al, 2018;Das, 2019;Li, 2023). The findings of this study showed that Rogers' Diffusion of Innovation model is an effective model for curriculum change involving the adoption of technology.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Principals must play multiple roles to keep the institutions running, manage teachers and students, and implement and manage curriculum change. Technology integration in education is an idea far from new, but technology in teaching mathematics still faces various challenges (see Abdullah et al, 2016;Daher et al, 2018;Das, 2019;Li, 2023). The findings of this study showed that Rogers' Diffusion of Innovation model is an effective model for curriculum change involving the adoption of technology.…”
Section: Discussionmentioning
confidence: 76%
“…However, several factors affect the use of technology in math education, including teacher-driven and non-teacher-driven factors. Teacher-driven factors that influence technology integration in math education include teacher's beliefs and attitudes (Abdullah et al, 2016;Daher et al, 2018;Ince-Muslu & Erduran, 2021;Li, 2023); teachers' confidence in using technology (Abdullah et al, 2016;Ince-Muslu & Erduran, 2021), and teacher's technological, pedagogical, and content knowledge (TPACK) (Li, 2023). Non-teacher-driven factors include access to teacher training and professional development opportunities, access to resources and support required for technology integration (Abdullah et al, 2016;Das, 2019;Ince-Muslu & Erduran, 2021), and students' readiness and expectations (Ince-Muslu & Erduran, 2021).…”
Section: Technology Integration In Teaching Mathematicsmentioning
confidence: 99%
“…TPACK framework enables teachers to navigate the digital landscape and employ technology to optimize mathematics teaching and learning experiences (Schmidt et al, 2009). Therefore, using a subject-oriented TPACK scale to evaluate teachers' knowledge to integrate digital technologies in teaching mathematics becomes crucial in the current era (Li, 2023). This study designed SMTTS to comprehensively measure secondary mathematics teachers' knowledge of integrating digital technologies in classroom teaching to fill the gap.…”
Section: Discussionmentioning
confidence: 99%
“…It allows for more accurate measurement of secondary mathematics teachers' TPACK competencies, ensuring that the scale adequately captures the knowledge and skills necessary for effective technology integration in mathematics education. By adopting a subject-oriented approach in the design of TPACK scale, researchers can gather more detailed insights into the specific technology integration practices and challenges faced by mathematics teachers (Li, 2023). SMTTS scale enables a more targeted approach to professional development and support initiatives, helping mathematics teachers enhance their abilities to integrate digital technologies into their instructional practices effectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation